Klasifikasi Jenis Daging Sapi Dan Kuda Menggunakan Metode Support Vector Machine (SVM) - Nisa', Widiana Kholisatun; Azizah, Nur; Agustin, Soffiana (INTRO : Journal Informatika dan Teknik Elektro, 2024)
ABSTRACT Meat is a crucial component in daily dietary intake due to its high protein content, which supports human intelligence and stamina. However, the similarity in color and texture among various types of meat often makes it difficult to distinguish between them. This can be exploited by unscrupulous meat vendors to substitute or mix meat types, leading to serious health implications. Meat types can be differentiated by observing the fibers and color of the meat. This research aims to address this issue by focusing on the differences in meat color and texture identified as potential solutions through digital image processing.One effective approach proposed is using the support vector machine (SVM) method with HSV feature extraction to distinguish between beef and horse meat. This study adopts SVM and HSV feature extraction in recognizing beef and horse meat types with a satisfactory accuracy rate of 93.3%. This indicates significant potential in accurately identifying meat types using this technology.